Antimicrobial efficacy of superoxide water as an intracanal irrigant in primary anterior teeth against facultative anaerobes: A randomized clinical trial - Deepika Narasimha Chari; Bhavna Haresh Dave (SRM Journal of Research in Dental Sciences, 2023)
Background: There is always a call for a search for an irrigating solution that can mask the disadvantages and simultaneously have antimicrobial action when used in root canals (RCs) at par with that of the most commonly used irrigants. Aim: The aim of this study was to evaluate the efficacy of superoxide water (SOW) to 1% sodium hypochlorite (NaOCl) and 2% chlorhexidine gluconate (CHX-G) when used as RC irrigants in primary anterior teeth against facultative anaerobes. Materials and Methods: A triple-blinded randomized clinical trial was carried out among children between the age groups of 3 and 7 years. Sixty teeth were randomly grouped into three groups: Group I: 1% NaOCl irrigation, Group II: 2% CHX-G irrigation, and Group III: SOW. Pre- and postirrigation samples using the paper points were sent to the microbial laboratory for the culture. Chi-square analysis and analysis of variance were carried out to find the significance of study parameters on the categorical scale and between the groups, respectively. Results: All the three irrigating solutions showed a statistically significant reduction in the microbial count of facultative anaerobes when pre- and postirrigating samples were compared. Conclusion: All the three solutions had almost similar antimicrobial efficacy. SOW was found to have similar effects on facultative anaerobes as that of NaOCl. Hence, SOW can be used as an alternative to NaOCl in the pediatric population.